Analysis of seawater quality in Gili Air North Lombok District - Tina Melinda; Nurhidayah Nurhidayah (Jurnal Pijar Mipa, 2023)
The research aims to identify seawater quality conditions (physical and Chemical) in Gili Air Lombok and determine the water quality status using the pollution index method based on the Indonesian Minister of Environment Decree No. 115/2003. The method is descriptive research with quantitative and qualitative approaches. To identify water quality by comparing it with PP No. Water quality standard. 82/2001 concerning Water Quality Management and Water Pollution Control which includes physical parameters and chemical parameters. The water quality of Gili Air-sea based on the water pollution parameter test shows that the physical quality parameters still meet the required quality standards except for two chemical quality parameters. The pH of 6.3, and Phosphate has a value of 0.1 mg/l, which exceeds the quality standard seawater for marine tourism. Dissolved Phosphate in Gili Air waters comes from demineralization from the bottom of the waters in the form of coral. The movement of seawater accelerates demineralization. Phosphate in Gili Air waters also comes from seagrass productivity in these waters. However, the phosphate levels in the waters of Gili Air do not endanger the life of aquatic biota and do not interfere with the aesthetics of tourism. Meanwhile, based on the assessment of the status of water quality using the pollution index method. It was shown to be very lightly polluted with an IP value of 2.622.